Descripción anatómica del xilema de la rama de Parkia igniflora Ducke “goma pashaco”, Eschweilera rufifolia S. A. Morí “machimango colorado”, Trichilia maynasiana C. DC “requia negro” del arboreto “El Huayo”. Puerto Almendras, Iquitos. 2021 - Utia Cumpa, Dennis Anderson (2022)
In the present study the anatomical description of the branch xylem of three forest species Parkia igniflora Ducke "Goma pashaco", Eschweilera rufifolia S. A. Morí "Machimango colorado", Trichilia maynasiana C. DC "Requia negro del Arboreto "El Huayo", Puerto Almendras - Iquitos. Applying the methodology of Valderrama (217, p 175). The species Parkia igniflora Ducke", presents an average tangential diameter of 187.91 ?m, classified as medium, with an average pores/mm2 of 3.56, classified as few, the average length of the vascular elements was 255.09 ?m classified as large, the rays have an average height of 245.04 ?m, classified as very short; having 24.71 ?m wide on average, classified as very fine. The average fiber length is 570.07 ?m, classified as short; being total fiber diameter 38.79 ?m, classified as medium; cell wall thickness on average gave 7.70 ?m, classified as thin. The species Eschweilera rufifolia S. A Morí, average tangential diameter 171.93 ?m, classified as medium. On average 6 pores/mm2, classified as few numerous. Average length of vascular elements 243.37 ?m classified as short, rays average height 791.95 ?m, classified as short; with 41.91 ?m average width, classified as fine. On average 9 rays/mm, classified as few abundant. Fibers average length 1071.36 ?m, classified as medium; on average 19.97 ?m total diameter, classified as narrow; thick-walled average thickness 6.63um. and the species Trichilia maynasiana C. DC, average tangential diameter 91.61 ?m, classified as small. On average 15.56 pores/mm2, classified as numerous. Average length of vascular elements 378.76 ?m classified as medium, rays average height 307.40 ?m, classified as very short; 29.07 ?m average width, classified as very fine. On average 9.68 rays/mm, classified as few abundant. Fibers average length 662.66 ?m, classified as short; on average 12.86 ?m total diameter, classified as narrow; very thick-walled with average thickness of 4.62 ?m.